Validation of Relationship between Patients' Descriptions of Pruritus and Patient-burden of Chronic Pruritus using Structural Equation Modelling - Ji Hoon Ryoo; Seon Hwa Lee; Dae-Lyong Ha; Kyung Duck Park; Jaehee Rho; Gyeong-Hun Park; Byung-Soo Kim; Kapsok Li; Chang Ook Park; Hye One Kim; Hei Sung Kim; Min Soo Jang; et al. (Medical Journals Sweden, 2022)
Patients with chronic itch describe their pruritus in a wide variety of ways. However, these subjective descriptions are often not taken into consideration by physicians. This study aimed to validate patients' descriptions of pruritus, and to investigate the relationship between various descriptions of pruritus and the patient burden of chronic pruritus by examining the mediating effects of sleep disturbance and sexual dysfunction on patient's quality of life, as predicted by various descriptions of pruritus. Exploratory and confirmatory factor analyses were performed to identify the factor structure measured by 11 descriptions of pruritus. The study then analysed differences in the degree of sleep disturbance, sexual dysfunction, and quality of life deterioration factors using a structural equation modelling method. Using data from 419 patients with chronic pruritus, 11 descriptions of pruritus were classified into 2 groups: (i) sensory pruritus (i.e. stinging, stabbing, burning, painful, formication, throbbing, and cold) that are linked with descriptions of pruritus patterns; and (ii) affective pruritus (i.e. annoying, unbearable, worrisome, and warm) from patient reports of psychological or emotional distress. The study found that affective pruritus decreases patient's quality of life either directly or indirectly through sleep disturbance. In conclusion, clues about a patients' sleep disturbance or poor quality of life can be obtained through their descriptions of pruritus.